Thermal properties of asphalt pavements under dry and wet conditions. (5th February 2016) - Hassn, Abdushaffi; Chiarelli, Andrea; Dawson, Andrew; Garcia, Alvaro
Abstract: Air voids play an important role in the temperature evolution of asphalt pavements exposed to the sun's radiation and the environment, but their effects have never been precisely quantified before. The objective of this article is to understand and quantify the effect of air voids on the temperature evolution of asphalt mixture under dry and wet conditions. To achieve this objective, dry and saturated asphalt slabs with different air voids contents have been exposed to infrared light and the surface and bottom temperature evolution, heat flux and evaporation rate have been measured. It was observed that under dry conditions air voids simply affect the specific heat capacity and thermal conductivity of asphalt mixture, while under wet conditions the energy used by water for evaporation reduces drastically the temperature of asphalt mixture. This has significance for Urban Heat Island mitigation amongst other implications. Graphical abstract: Highlights: Dry and saturated asphalt mixture slabs have been exposed to an energy source. The temperature evolved differently according to the moisture and air voids. The mechanisms of heat transfer in asphalt mixture have been explained.